‘Talk Me : Aplikasi Pendukung Media Komunikasi Nonverbal Penyandang Tunarungu Dalam Meningkatkan Kemampuan Berinteraksi Sosial Di Kota Ternate - Lisda Simabur; Effendi M; Zainuddin Zainuddin; MS Ahmad (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
Communication which is an important requirement in human life is not limited to certain groups. This need is needed by every human being from the time he is born until the end of time. Deaf people prefer to form groups and gather together to get comfort when meeting and chatting with each other. The research was conducted by applying a qualitative research method based on a descriptive approach. Data collection techniques in the form of interviews and observations to obtain relative and objective information. Interviews were conducted with four informants, namely: the head of the Ternate City Deaf Association, two Teachers who implement the SIBI language in the field of Education (Ternate City Special School) and one member of the General Public. The data analysis techniques used are literature study, data collection, drawing conclusions from FGD data), needs analysis, system design, implementation, and testing. Based on the results of the research, the main problem that occurs is the lack of interest and digital-based communication tools which are quite a big problem in helping the listening community in carrying out social interactions. And the results of making an application by applying the CNN analysis method to the Talk me application obtained quite good results and were close to the maximum results, the application sensitivity feasibility trials obtained quite good results and were close to the maximum value, the average score for 50 trials was 0, 913793, where the data will be said to be very good if the trial value is close to 1, and for the loss value (not sensitive) the average is 0.04265